Виртуальные медиа в новейшей русскоязычной драматургии - Maroń, Anna (Studia Rossica Posnaniensia, 2026)
The article explores the influence of digital and multimedia technologies on Russian and Russian-language drama of the 21st century. It analyzes plays in which virtual communication becomes not only a thematic, but also a structural element of the dramatic text. The study aims to identify the ways in which the virtual world and media culture are represented, as well as to define the poetics of digital interaction and the transformation of dramatic form under the impact of digital media. Special attention is given to the language of online communication and the reflection of the spiritual crisis of the individual in conditions of digital dependence. The study shows that the Internet functions not only as a setting but also as an autonomous character shaping the dramaturgical dynamics of the work. The author highlights the key functions of virtual space: structural, thematic, symbolic, and psychological demonstrating that the Internet and social networks determine the narrative logic, text aesthetics, and modes of audience perception. The article concludes that a new artistic model of “virtual drama” is emerging, in which dramatic, media, and digital discourses intersect, reflecting the cultural specificity of the digital age.